Telaah Nilai-Nilai Pendidikan Karakter pada Santri Tahfidzul Qur'an - Fahrur Rozi, Ahmad (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2021)
Educational character constitutes major highlight in every educational institutes lately, yet in each educational program there particular methods and ways to challenge the problems such as moral degradation. In reality, pesantren (Islamic boarding school) becomes one of trusted institute to construct education based on character with one of its program, tahfidzul Qur’an. In the pesantren of Al Falah Al Makky, this tahfidzul Qur’an program also becomes one of effective method to construct education based on moral character. By this very reason, it quite imperative to analyze the values of this program and how this pesantren develop the Qur’anic methods among their students. This research method uses descriptive qualitative method by the first step, collecting the data, analyze, and making interpretations. This research method is conducted by survey, case study, comparative study, space and time study, behavioral and documentary analysis. The result of this research process shows that tahfidzul Qur’an program in Al Falah Al Makky pesantren emphasizes on some major moral characters in life: Shidd?q, am?nah, fath?nah, tabl?gh, being patient, istiqomah, being discipline, rigid, taqwa, birr al-w?lidayn, estrange the sin, be gratitude, socially sensitive and caring, kind-hearted, being sincere, being passionate and hard working.